Impacts of Spatial Intensity Policies on Jakarta Property Prices - Manahampi, Stevanus J.; Yudhistira, M. Halley (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
This study examines the effects of floor area ratio (FAR) and building coverage ratio (BCR) on property prices in Jakarta. Using a hdonic price mdel with data from property listings and a geographical information system (GIS) analysis, it explores how these regulations influence values across regions and property types, accounting for access to amenities and infrastructure. Results show FAR lowers prices in dense areas like Central Jakarta but raises them in less developed regions like East Jakarta. BCR effects are mixed, positive where infrastructure is strong but negative where it is weak, underscoring the need for context-specific urban planning.